Recommendations for the treatment of multiple sclerosis with disease-modifying drugs during the COVID-19 pandemic - Kizlaitienė , R.; Giedraitienė , N.; Sereikė , I.; Liutkienė , J.; Leščinskienė , L.; Kaubrys , G. (Neurologijos seminarai, 2020)
The novel coronavirus 2019 (COVID-19) and the subsequent pandemic present a challenge to neurologists treating patients with multiple sclerosis (MS) worldwide. Many national professional bodies have responded rapidly by issuing guidelines for the COVID-19 pandemic, primarily focused on MS disease-modifying therapies (DMTs). In this article, we review implications of COVID-19 for people with MS, including general health advice, the risk of respiratory infections, basic recommendations for relapse management, MS treatment, including disease-modifying therapies, and medical services for MS patients during the COVID-19 pandemic.